2012
DOI: 10.1111/j.1368-423x.2012.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental regression in partially linear models

Abstract: We consider the semiparametric regression X t β+φ(Z) where β and φ(•) are unknown slope coefficient vector and function, and where the variables (X, Z) are endogeneous. We propose necessary and sufficient conditions for the identification of the parameters in the presence of instrumental variables. We also focus on the estimation of β. An incorrect parameterization of φ may generally lead to an inconsistent estimator of β, whereas even consistent nonparametric estimators for φ imply a slow rate of convergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 31 publications
(52 reference statements)
3
42
0
Order By: Relevance
“…Because it is difficult to find a good parametric model for F (X i ), semiparametric regression that does not require one to specify a parametric model for F (X i ) is a potentially appealing alternative to TSLS. Robinson (1988), Ai and Chen (2003) and Florens, Johannes, and van Bellegem (2005) described approaches to semiparametric IV regression. Robinson (1988) showed that a √ N consistent estimate of α 0 in (1.2) can be obtained, as N → ∞, under certain smoothness conditions; Robinson's method is reviewed below.…”
Section: Semiparametric Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is difficult to find a good parametric model for F (X i ), semiparametric regression that does not require one to specify a parametric model for F (X i ) is a potentially appealing alternative to TSLS. Robinson (1988), Ai and Chen (2003) and Florens, Johannes, and van Bellegem (2005) described approaches to semiparametric IV regression. Robinson (1988) showed that a √ N consistent estimate of α 0 in (1.2) can be obtained, as N → ∞, under certain smoothness conditions; Robinson's method is reviewed below.…”
Section: Semiparametric Approachmentioning
confidence: 99%
“…Robinson (1988) showed that a √ N consistent estimate of α 0 in (1.2) can be obtained, as N → ∞, under certain smoothness conditions; Robinson's method is reviewed below. Ai and Chen (2003) considered more general semiparametric problems, and Florens, Johannes, and van Bellegem (2005) focused on the partial linear IV model but allowed X i to be endogenous. The difficulty with these semiparametric approaches is that, even when they are √ N consistent, when X i is of moderate or high dimension relative to the sample size, the semiparametric estimators' finite sample behavior deteriorates because of the curse of dimensionality (see, e.g., Robins and Ritov (1997)).…”
Section: Semiparametric Approachmentioning
confidence: 99%
“…3 See Darolles et al (2003) or Hall and Horowitz (2005). 4 See Darolles et al (2003) and Florens et al (2006). This term represents the difference between the true function and the regularized solution of the 'true' problem T ϕ = r ((αI + T * T ) −1 T * T ϕ).…”
Section: Asymptotic Propertiesmentioning
confidence: 99%
“…In fact, the estimation error associated withK (n) is negligible with respect to the other terms in the bias and variance. In the following theorem we focus on the consistency ofÊ α (ϕ|y (n) ); consistency ofμ Theorem 4 Let ϕ * be the true value having generated the data y (n) under model (4) and µ y α be a gaussian measure on L 2 F (Z) with mean and covariance operator defined in (14). Under Assumptions 4 and 5, if α n → 0 and α 2 n n → ∞, we have ||Ê α (ϕ|y (n) ) − ϕ * || 2 → 0 in Pf ,ϕ * ,w -probability and if δ * ∈ Φ β , for some β > 0,…”
Section: Unknown Infinite Dimensional Parametermentioning
confidence: 99%